2017
DOI: 10.1016/j.maturitas.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Drug holidays from bisphosphonates and denosumab in postmenopausal osteoporosis: EMAS position statement

Abstract: Discontinuation of bisphosphonates should be considered in all patients who have beentreated for more than five years with alendronate, risedronate or zoledronic acid. In view of the limited evidence, no robust recommendations can be made for ibandronate and denosumab. If the patient has not experienced fractures before or during therapy and the fracture risk is low, a "drug holiday" canbe recommended. Although there is no solid evidence, 1-2 years for risedronate, 3-5 years for alendronate and 3-6 years for z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 59 publications
1
80
0
13
Order By: Relevance
“…After the start of the present study, several case reports and post hoc analyses of the extension of the randomized controlled Freedom study reported increased incidences of vertebral fractures after discontinuation of treatment with denosumab, especially in patients with prevalent vertebral fractures . The growing awareness of this rebound effect and the incidence of vertebral fractures have led to reviews of the literature and position statements from the European Calcified Tissue Society and the European Menopause and Andropause Society regarding the potentially negative effect on bone health after discontinuation of denosumab treatment . The societies recommend switching to other antiresorptive drugs and careful monitoring of patients when discontinuation of denosumab treatment has been decided.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…After the start of the present study, several case reports and post hoc analyses of the extension of the randomized controlled Freedom study reported increased incidences of vertebral fractures after discontinuation of treatment with denosumab, especially in patients with prevalent vertebral fractures . The growing awareness of this rebound effect and the incidence of vertebral fractures have led to reviews of the literature and position statements from the European Calcified Tissue Society and the European Menopause and Andropause Society regarding the potentially negative effect on bone health after discontinuation of denosumab treatment . The societies recommend switching to other antiresorptive drugs and careful monitoring of patients when discontinuation of denosumab treatment has been decided.…”
Section: Discussionmentioning
confidence: 84%
“…(34)(35)(36) The growing awareness of this rebound effect and the incidence of vertebral fractures have led to reviews of the literature and position statements from the European Calcified Tissue Society and the European Menopause and Andropause Society regarding the potentially negative effect on bone health after discontinuation of denosumab treatment. (37,38) The societies recommend switching to other antiresorptive drugs and careful monitoring of patients when discontinuation of denosumab treatment has been decided. Our study shows that the rebound effect is applicable also to periprosthetic bone in nonosteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal duration of a bisphosphonate drug holiday may likely be influenced by a number of variables, including baseline fracture risk, as well as changes in BMD and bone turnover markers (BTMs), fractures, altered risk factors, or changes in comorbidities that occur during the holiday. (7,13) However, the patient and provider factors associated with the suspension of bisphosphonates and restart of osteoporosis medications are not fully known at a population-level and might vary based on a number of factors including route of administration (ie, intravenous versus oral bisphosphonates) or drug affinity to bone. A previous analysis of Medicare data from 2006 to 2010 reported that baseline characteristics of patients (sex, race, income, number of visits) at the time of bisphosphonate treatment initiation were only weakly associated with subsequent discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…These agents function primarily by slowing bone resorption with the expectation that bone formation will continue at least to some extent. Atypical femur fractures and osteonecrosis of the jaw are significant concerns surrounding the use of these therapies …”
Section: Introductionmentioning
confidence: 99%
“…Atypical femur fractures and osteonecrosis of the jaw are significant concerns surrounding the use of these therapies. (4,5) Low-dose pulse parathyroid hormone peptides represent another important advance in the treatment of age-related and postmenopausal osteoporosis. (6) Unfortunately, their use is recommended for 2 years due to an osteosarcoma concern.…”
Section: Introductionmentioning
confidence: 99%